Phase-shifter-less Vortex Electromagnetic Wave Generation Technology with Tunable Topological Charge/Steering Angle under Random Initial Phase Condition of Phase-locked Source - Zhou, Yuliang; Yao, Kaiyuan; Li, Xiaona; Huang, Yong Mao; Jin, Haiyan (Applied Computational Electromagnetics Society Journal (ACES), 2023)
This paper demonstrates how to implement a vortex electromagnetic wave generation system with beam steering using only delay lines as phase-shifting elements. The system is based on uniform circular array and phased array technology. A detailed theoretical derivation is presented, which yields an input frequency matrix corresponding to each target case. Furthermore, considering the random initial phase problem of the actual phase-locked source, the above scheme is further improved in this paper. By cleverly setting the circuit structure, the influence of the initial phase inconsistency on the phase control system is filtered out. The performance is verified by analytical calculations and full-wave electromagnetic simulations, which are in good agreement with the proposed theory. The scheme proposed in this paper can completely get rid of the phase shifter and realize the free adjustment of the topological charge number/beam steering angle. The adjustment accuracy depends on the tuning accuracy of the phase-locked source, which can achieved an accuracy over 1Hz at a cost of less than six dollars, which makes it an interesting and flexible low-cost vortex electromagnetic wave generation scheme.